Answers

2015-04-05T16:53:33+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
A₁ = r  <  0            the first number of AP is less than zero.
   a_k =  0,      k > 0

It means that  common difference d  is positive.
 a_k = a₁ + (k-1) d  = 0
       = r + (k-1) d = 0
  =>   d = - r / (k -1)

 S_2k-1  = sum of 1st 2k-1 terms of the AP
          = [ 2 a₁ + (2k-2) d ] (2k-1)/2
          = [ 2 r  -  2 (k-1) r /(k-1) ] *(2k -1) /2
           = 0
============
it is seen that a_1 to  a_k-1  are negative.  a_k = 0.
         a_k+1 to  a_2k-1 are positive.    These k-1 terms are symmetrically equal to  a_1 to a_k-1 , but opposite in sign.
   Thus the sum  a_1 +.... + a_k-1 + a_k + a_k+1 + ..... + a_2k-1  =  a_k = 0

1 5 1